Aryltetralin lignans from Linum mucronatum Bertol. ssp mucronatum - Koulman, A; Konuklugil, B; Evren, H (Springer, 2005)
The dried and aerial part of Linum mucronatum ssp. mucronatum was analyzed by gas chromatographymass spectrometry (GC-MS). Two aryltetralin lignans, podophylloyoxin, 6-methoxypodophylloyoxin, and P-peltatin, were identified. This is the first report of the analysis of L. mucronatum ssp. mucronatum.
Keywords: Linum mucronatum ssp mucronatum; lignan; aryltetralin lignan